Heterogeneity amongst GLP-1 RA cardiovascular outcome trials results: can definition of established cardiovascular disease be the missing link? - Melo, Miguel (2021)
Atherosclerotic cardiovascular diseases are the leading cause of adverse outcomes in patients with type 2 diabetes, and all new anti-diabetic agents are mandated to undergo cardiovascular outcome trials (CVOTs). Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are incretin mimetics that reduce blood glucose levels with a low associated risk of hypoglycaemia. CVOTs with different GLP-1 RAs yielded different results in terms of major cardiovascular composite outcome (MACE), with some trials showing superiority in the treatment arm, whereas other simply displayed non-inferiority. More importantly, the significance of each component of MACE varied between drugs. This begs the question of whether these differences are due to dissimilarities between drugs or other factors, namely trial design, are at the root of these differences. We analyse the trial designs for all CVOTs with GLP-1 RAs and highlight important differences between them, namely in terms of definition of established cardiovascular disease, and discuss how these differences might explain the disparate results of the trials and preclude direct comparisons between them. We conclude that a fair comparison between GLP-1 RA CVOTs would involve post-hoc analysis re-grouping the patients into different cardiovascular risk categories based upon their baseline clinical parameters, in order to even out the criteria used to classify patients.